2021
DOI: 10.1186/s12870-021-03073-8
|View full text |Cite
|
Sign up to set email alerts
|

Expressional diversity of grapevine 3-Hydroxy-3-methylglutaryl-CoA reductase (VvHMGR) in different grapes genotypes

Abstract: Background 3-Hydroxy-3-methylglutaryl-CoA reductase (HMGR) is a key enzyme in the mevalonate (MVA) pathway, which regulates the metabolism of terpenoids in the cytoplasm and determines the type and content of downstream terpenoid metabolites. Results Results showed that grapevine HMGR family has three members, such as VvHMGR1, VvHMGR2, and VvHMGR3. The expression of VvHMGRs in 'Kyoho' has tissue specificity, for example, VvHMGR1 keeps a higher expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…A previous study by Zheng et al found a light-induced reduction in HMGR activity in grapevine, suggesting a direct or indirect role of HMGR in light sensing, which may also be reflected in our observations. 48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study by Zheng et al found a light-induced reduction in HMGR activity in grapevine, suggesting a direct or indirect role of HMGR in light sensing, which may also be reflected in our observations. 48 …”
Section: Resultsmentioning
confidence: 99%
“…A previous study by Zheng et al found a light-induced reduction in HMGR activity in grapevine, suggesting a direct or indirect role of HMGR in light sensing, which may also be reflected in our observations. 48 However, the response to light was impaired, especially by bentazon. The biological processes most strongly regulated by bentazon were cellular response to blue light and the light stimulus, response to red or far-red light, and the blue light signaling pathway.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the regulatory effect of B. cereus was different under control and salt stress conditions. HMGR acts as the catalyst for the first committed reaction of the mevalonate pathway, which is critical for plant adaptations against harsh environmental conditions ( Zheng et al, 2021 ), so the expression level of HMGR gene was higher by B. cereus under salt stress. Moreover, B. cereus upregulated the expression level of many key genes of G. uralensis in both control and salt stress conditions, but only increased the content of liquiritigenin under the control condition and increased the contents of glycyrrhizic acid and glycyrrhetinic acid under the salt stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…These results enabled the enhancement of the latex yield of transgenic rubber plants (Jayashree et al, 2018). There are three members of the HMGR gene family ( VvHMGR1 , VvHMGR2 , and VvHMGR3 ) in V. vinifera that show different expression patterns during different developmental stages and in different tissues (Zheng et al, 2021). It has been extensively shown that HMGRs have different regulatory modalities and divergent physiological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the DXS gene enhances the production of terpenoidal secondary metabolites in homologous as well as heterologous plant systems (Jadaun et al, 2017). In general, at least one copy of HMGR has been identified and isolated in several plants, including Andrographis paniculata , Vitis vinifera , and Pogostemon cablin (Srinath et al, 2020; Zhang et al, 2019; Zheng et al, 2021). Overexpression of the HMGR gene from Hevea brasiliensis in transgenic tobacco plants enhanced the accumulation of total sterols up to six‐fold (Schaller et al, 1995).…”
Section: Discussionmentioning
confidence: 99%